Implementasi Program Kerja PKK (Pemberdayaan dan Kesejahteraan Keluarga) dalam Pemberdayaan Ekonomi Rumah Tangga di Desa Ratna Chaton Kecamatan Seputih Raman Kabupaten Lampung Tengah - Destri Rahmawati (Mau'idhoh Hasanah, 2019)
ABSTRACT This study discusses the Implementation of PKK (Empowerment and Family Welfare) Work Program in household economic empowerment in Ratna Chaton Village, Seputih Raman District, Central Lampung Regency. This research includes field research (Field Research) which is a study conducted systematically by raising the data in the field. While its nature is descriptive, that is to make a picture or painting systematically, factually, and accurately about the facts, the characteristics and the relationship between the phenomena under investigation. In collecting data using the interview method, observation method and documentation method. The authors' research findings show that the implementation of the PKK work program in household economic empowerment in the Ratna Chaton Village of Seputih Raman District through the UPPK (Family Revenue Improvement Efforts) program has led to a successful economic empowerment program, the implementation of which is entrepreneurship training, venture capital lending, and developing productive household businesses. Housewives experience changes by being able to explore the abilities they have, increasing living standards and housewives can be independent by developing their businesses and can generate household economic income.